Recent Advances in Defining the Immunoproteome of Mycobacterium tuberculosis - Kunnath-Velayudhan, Shajo; Porcelli, Steven A. (Frontiers in Immunology, 2013)
Immunity conferred by antigen-specific CD4+ T cells is critical for controlling infection with Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis. However, despite research that spans more than a century, many of the characteristics of protective immune responses to Mtb remain elusive. Defining the repertoire of antigenic targets is central to understanding the immune response against this pathogen. Although traditional methods of antigen discovery have identified many immunodominant antigens, they afford limited proteome coverage. Recent advances in proteomic techniques that are based on peptide library and protein microarray technology have enabled interrogation of the entire proteome of Mtb for antigens. Though these techniques have limitations and are still evolving, early studies using these techniques provide an unbiased view of the immune response to Mtb. Here we review proteome-wide approaches to antigen discovery and summarize what these have revealed so far on the composition of the Mtb immunoproteome.